Social structuring of language and the mobility of semiotic resources across the linguistic landscapes of Zambia: A multimodal analysis - Jimaima, Hambaba (University of the Western Cape, 2016)
Philosophiae Doctor - PhD === The current study framed as Social Structuring of Language and the Mobility of Semiotic Resources across the Linguistic Landscapesof Zambia: A Multimodal Analysis, is situated in Lusaka and Livingstone and their selected surrounding peri-urban and rural spaces (of Kabanana, Bauleni and Chipata; Kafue, Chongwe, Chief Mukuni’s area and stretches between Livingstoneand Zimba and Livingstone and Kazungula). The study aims to explore the linguistic landscapes (LL) of these urban, peri-urban and rural spaces in order to gain insight into the social structuring of language and the mobility of semiotic resources across the LL. This entails an understanding of how languages are distributed and realized across the research sites. In particular, the study aims at understanding how the regionalization of languages is (re-)produced, contested and maintained in (and beyond) the territories for which they are promulgated for use. Thus, the study foregrounds the mobility of the semiotic resources across the LL. In essence, artefactual material, symbols including languages are, in a multimodal fashion, investigated to see their pliability and mobility from context to context. In the light of the mobility of the semiotic resources, the study privileges both translocal and transnational mobility as the force behind the movement and the dispersal of the semiotic material across ethnolinguistic, formal, informal, urban and rural boundaries. This meant understanding the kind of signs in both urban and rural areas and why they are emplaced in the broader context of sign/place-and meaning making. In order to achieve the aim and objectives, the study has been foregrounded in ethnographic research paradigm in which walk, gaze, talk (interview) and photography were of irreplaceable importance. The conflation of walk, gaze (observation), talk and photography in one investigation avails much. Firstly, the walk brought the researcher within the allowable observation range in order to gain an insider impression while, at the same time, maintaining the objectivity required for an unbiased analysis. Participant observation coupled with gaze offered the required positioning for carrying out a multimodal analysis especially in the rural areas which turned out to have the paucity of signage. Thus, by being a participant observer, I keenly observed how sign-and meaning making were accomplished in oral-dominant communities. This meant positioning oneself as a new comer needing direction. It was in such moments when practices of sign-and meaning making were observed and recorded. For example, I would ask: how do I get to the next village/school/headman? The reference to ecological features such as trees, hills and streams extended the taxonomy of signs available for use in rural areas. Interviews with business owners about the emplaced signs brought to the fore the hidden narratives often gushing out from individualized orientation and personal experiences, as well as the shared sociocultural knowledge and histories of both the producer and consumers of the multimodal LL. Photography yielded digital images forming not only the quantitative data but also the qualitative one upon which a multimodal analysis was done. The aim was to capture over 1500 of images which were to be processed by the Software Package of the Social Sciences (SPSS). Over 1500 images were collected but only 1157 were coded based on the languages present, materiality, inscription, and emplacement. The quantitative data arising from this exercise provided insight into the social structuring of language and mobility of the semiotic resources across the urban, peri-urban and rural spaces. These results were later compared with the national census reports. The analysis of images as qualitative data availed much about the multimodal nature of the signage in place. The analysis of the qualitative data was accomplished by multimodality in its evolve form. Kress and Van Leeuwen’s(2006) Grammar of Visual Design, Scollon and Sollon’s (2003) Geosemiotics, and theoretical concepts such as resemiotization, remediation, recontextualization, decontextualization, multivocality and metamorphosis provided a sound theoretical toolkit to analyse the multimodal/multisemiotic signage emplaced across the public spaces of the research sites. As a result of a robust methodology and theoretical base, the study was able to underpin the social structuring of language and the mobility of semiotic resources across the linguistic landscapes in a manner too apparent. First, apart from showing the linguistic heterogeneity of the research sites, the study shows that social structuring of languages being experienced is one that is predicated on predictability, flexibility, flux and indeterminacy. The results showing the social structuring of English, for example, demonstrate the uneven spread of English across the urban, peri-urban and rural spaces. In particular, the results go against the normative expectation that the urbanized centres of Lusaka and Livingstone would have more signs in English. Peri-urban (Kabanana) and rural (Chongwe/Kafue) spaces showed more signs in English. This suggests a disembodiment of language and locality as well as social actors. Moreover, the results showed the co-occupancy of English and local languages in one micro-space/time. This entails the blurring of boundaries between languages of different socio-political statuses. The bilingualsigns on which English and non-regional languages occur demonstrate the persistent percolation of minor languages onto the LL. The presence of regional languages, albeit differentially, in and beyond their regions for which they were promulgated reminds us that there is a counter hegemonic narrative going on in the LL of the research sites –in defiance of regionalization (zoning). Thus, the results show that languages in the research sites do not stay put where they are officially put by legislation. The conflation of multiple semiotic resources has further (re-)produced linguistic coinages resulting in what I refer to as a sociolinguistics of amalgamation predicated on hybridity, fusion and tr ans languaging. This evidence is framed within the trans local and transnational mobility where both the social actors and the semiotic resources are constantly in circulation. The study observes that mobility is not only restricted to local circulation of cultural materialities from urban to rural and rural to urban,but also a more transnational circulation of semiotic resources. For example, the ubiquitous spread of Chinese signage across the urban, peri-urban and rural LL accentuates the permeating effect of translocal and transnational mobility, leading to the de-territorialization of spaces. The study further shows the sociocultural narratives in place-and meaning making. Place and meaning making as an agentive act is premised on shared sociocultural knowledge and histories (Kress 2010), but is further exploited and extended by creatively drawing on individualized orientation, experiences and subjective sensibilities. In this regard, the study agrees with Hult (2009) that in order to glean the subjective narrations and re-imagining of space embedded in the emplaced signs, interviews with the owners of the emplaced signs is in dispensible. Thus, like Blommaert (2012) aptly suggests, spaces are semiotized as themed spaces. The study has shown how spaces are Christianized, moralized, gendered and anonymized, thus, gaining insight into the forces and meanings behind both the emplacement of and emplaced signs. Further, the reading of artefacts in Livingstone Museum shows how the juxtaposition of the material culture of multilingualism and multiculturalism is a semiotic strategy to double-articulate multiple localities simultaneously: local and global; familiar and unfamiliar; modern and tradition. The transaction of multi vocality in a single moment of emplacement and gaze transforms space dramatically and extends the meaning potential of the emplaced signage in micro-space/time. Further, the observable paucity of signs in rural areas forces us to defer to an ecological approach in which oral language mediation, recycling and repurposing of material affordances provide a comprehensive account of the signage and sign-making/consumption in place. form. Kress and Van Leeuwen’s(2006) Grammar of Visual Design, Scollon and Sollon’s (2003) Geosemiotics, and theoretical concepts such as resemiotization, remediation, recontextualization, decontextualization, multivocality and metamorphosis provided a sound theoretical toolkit to analyse the multimodal/multisemiotic signage emplaced across the public spaces of the research sites. As a result of a robust methodology and theoretical base, the study was able to underpin the social structuring of language and the mobility of semiotic resources across the linguistic landscapes in a manner too apparent. First, apart from showing the linguistic heterogeneity of the research sites, the study shows that social structuring of languages being experienced isone that is predicated on unpredictability, flexibility, flux and indeterminacy. The results showing the social structuring of English, for example, demonstrate the uneven spread of English across the urban, peri-urban and rural spaces. In particular, theresults go against the normative expectation that the urbanized centres of Lusaka and Livingstone would have more signs in English. Peri-urban (Kabanana) and rural (Chongwe/Kafue) spaces showed more signs in English. This suggests a disembodiment of language and locality as well as social actors. Moreover, the results showed the co-occupancy of English and local languages in one micro-space/time. This entails the blurring of boundaries between languages of different socio-political statuses. The bilingualsigns on which English and non-regional languages occur demonstrate the persistent percolation of minor languages onto the LL. The presence of regional languages, albeit differentially, in and beyond their regions for which they were promulgated reminds us that there is a counter hegemonic narrative going on in the LL of the research sites –in defiance of regionalization (zoning). Thus, the results show that languages in the research sites do not stay put where they are officially put by legislation. The conflation of multiple semiotic resources has further (re-)produced linguistic coinages resulting in what I refer to as a sociolinguistics of amalgamation predicated on hybridity, fusion and translanguaging. This evidence is framed within the translocal and transnational mobility where both the social actors and the semiotic resources are constantly in circulation. The study observes that mobility is not only restricted to local circulation of cultural materialities from urban to rural and rural to urban,but also a more transnational circulation of semiotic resources. For example, the ubiquitous spread of Chinese signage across the urban, peri-urban and rural LL accentuates the permeating effect of translocal and transnational mobility, leading to the de-territorialization of spaces. The study further shows the sociocultural narratives in place-and meaning making. Place and meaning making as an agentive act is premised on shared sociocultural knowledge and histories (Kress 2010), but is further exploited and extended by creatively drawing on individualized orientation, experiences and subjective sensibilities. In this regard, the study agrees with Hult (2009) that in order to glean the subjective narrations and re-imagining of space embedded in the emplaced signs, interviews with the owners of the emplaced signs is indispensible. Thus, like Blommaert (2012) aptly suggests, spaces are semiotized as themed spaces. The study has shown how spaces are Christianized, moralized, gendered and anonymized, thus, gaining insight into the forces and meanings behind both the emplacement of and emplaced signs. Further, the reading of artefacts in Livingstone Museum shows how the juxtaposition of the material culture of multilingualism and multiculturalism is a semiotic strategy to double-articulate multiple localities simultaneously: local and global; familiar and unfamiliar; modern and tradition. The transaction of multivocality in a single moment of emplacement and gaze transforms space dramatically and extends the meaning potential of the emplaced signage in micro-space/time. Further, the observable paucity of signs in rural areas forces us to defer to an ecological approach in which oral language mediation, recycling and repurposing of material affordances provide a comprehensive account of the signage and sign-making/consumption in place.